Comparing the accuracy of brief versus long depression screening instruments which have been validated in low and middle income countries: a systematic review - Akena Dickens; Joska John; Obuku Ekwaro A; Amos Taryn; Musisi Seggane; Stein Dan J (BMC Psychiatry, 2012)
Abstract Background Given the high prevalence of depression in primary health care (PHC), the use of screening instruments has been recommended. Both brief and long depression screening instruments have been validated in low and middle income countries (LMIC), including within HIV care settings. However, it remains unknown whether the brief instruments validated in LMIC are as accurate as the long ones. Methods We conducted a search of PUBMED, the COCHRANE library, AIDSLINE, and PSYCH-Info from their inception up to July 2011, for studies that validated depression screening instruments in LMIC. Data were extracted into tables and analyzed using RevMan 5.0 and STATA 11.2 for the presence of heterogeneity. Results Nineteen studies met our inclusion criteria. The reported prevalence of depression in LMIC ranged from 11.1 to 53%. The area under curve (AUC) scores of the validated instruments ranged from 0.69-0.99. Brief as well as long screening instruments showed acceptable accuracy (AUC≥0.7). Five of the 19 instruments were validated within HIV settings. There was statistically significant heterogeneity between the studies, and hence a meta-analysis could not be conducted to completion. Heterogeneity chi-squared = 189.23 (d.f. = 18) p<.001. Conclusion Brief depression screening instruments in both general and HIV-PHC are as accurate as the long ones. Brief scales may have an edge over the longer instruments since they can be administered in a much shorter time. However, because the ultra brief scales do not include the whole spectrum of depression symptoms including suicide, their use should be followed by a detailed diagnostic interview.